Anticancer Alkaloids from Trees: Development into Drugs - Isah, Tasiu (Pharmacognosy Reviews)
Trees have made an enormous phytochemical contribution in anticancer drugs’ development more than any other life form. The contributions include alkaloids that are biosynthesized in various ways and yield. Lead alkaloids isolated from the trees are taxol and camptothecins that currently have annual sales in billion dollars. Other important alkaloids isolated from these life forms include rohitukine, harringtonine, acronycine, thalicarpine, usambarensine, ellipticine, and matrines. Studies on their mechanism of action and target on the DNA and protein of cancerous cells aided the development of potent hemisynthesized congeners. The molecules and their congeners passed/are passing a long period of historical development before approved as antineoplastic drugs for cancer chemotherapy. Some of them did not find the application as anticancer drugs due to ineffectiveness in clinical trials; others are generating research interest in the antineoplastic activity at the present and have reached clinical trial stages. Potentials in antineoplastic molecules from trees are high and are hoped to be commensurate with cancer types afflicting human society in the future.
Keywords: Alkaloids; camptothecin; cancer; natural products; taxol; trees